(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The Statistical representation of the complex traffic flow system for the cause of distinguishing as well as forecasting the functioning of traffic is known as Traffic flow modelling. The principal basis of several traffic flow models is represented by traffic stream models. Traffic stream models show us the basic interrelationship among the three basic traffic flow variables i.e., speed of vehicle, flow of vehicle and density of vehicles. Interpretation of the traffic flow variables, their interdependence and approach to model traffic are extremely crucial in the designing, operating and planning of transit systems. Numerous ground work research has been done recommending various traffic stream models. Designing of transit systems is a complex problem and includes various key parameters like: road type, road width, width of vehicle, Cross-section of road, Number of lanes etc. Designing of roads takes place according to the recommendations of Indian Road Congress. In this paper various values obtained from observations on local data were done involving traffic flow. The purpose of this research is to study and examine the traffic flow on lanes in order to explore a model which will allow continuous movement of traffic on the National Highway. A realistic perception of traffic flow pattern for such crucial roads is important for traffic functioning, organizing and administering for assuring the maximum level of service. Using elementary framework of traffic flow for the choice and location of selected road, width of road, sample time, survey of traffic, video recordings of traffic, as well as statistical inquiry and figuring of basic parameters of traffic flow has been done. This study will be done under the heterogeneous conditions of traffic on national highways and the values of various traffic flow variables will be extracted. These constants will help us in obtaining a link between various flow parameters like vehicle density, vehicle volume, vehicle speed etc., and in turn help us in obtaining graphical relations between various traffic parameters for the traffic network. This will help us in developing the theoretical relationship between various traffic flow variables which will in turn enable us to model for current roads.